The Relationship of Physical Activity with Relapse of Gastritis in Gastritis Patient - Diana Rachmania; Pria Wahyu Romadhon Girianto; K.H, Wilda Lintang (Journal of Applied Nursing and Health, 2021)
Background: Strenuous physical activity in gastritis sufferers must be considered because this disease is easy to relapse. Increased stomach acid is caused due to strenuous physical activity so that it can trigger an increase in stomach acid. This study aims to analyze the relationship between physical activity and relapse of gastritis in patients with gastritis. Methods: The research design used correlation with a cross-sectional approach. The population in this study was 63 and the number of samples was 54 selected by purposive sampling technique. The instrument used to collect data on physical activity and gastritis relapse was a questionnaire. Data analysis using Spearman Rank. Results: The results of the study found that most of the 59.3% of respondents included in the category of heavy physical activity and almost half of the respondents in the category of infrequent and occasional relapse had the same value, each of which was 40.7% of respondents. Analysis with the Spearman Rank statistical test got a p-value of 0.034 <0.05, meaning that there is a relationship between physical activity and the relapse of gastritis inpatient with gastritis. Conclusion: Strenuous physical activity can cause gastritis relapse. This condition occurs because the protective mechanisms in the stomach begin to decrease, causing inflammation, for this reason, patients are expected to be more careful with their daily physical activities to minimize the relapse of gastritis